1987
DOI: 10.1093/carcin/8.6.865
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of insulin-like growth factor II is not a necessary event in Wilms' Tumour progression

Abstract: Wilms' tumour (WT) is a paediatric kidney tumour arising from the embryonal metanephrogenic blastema. Recent reports suggest that the expression of messenger RNA (mRNA) for insulin-like growth factor II (IGFII) is elevated in WT. Total cytoplasmic RNA was extracted from 11 sporadic WTs and analysed for IGFII mRNA using dot-blot hybridization. The level of IGFII mRNA expression varied greatly and not all tumours displayed enhanced IGFII expression. Two successive WT xenografts were established in nude mice. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

1989
1989
2001
2001

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 0 publications
0
6
1
Order By: Relevance
“…In addition, they show a structural change of the I G F II gene in one Wilms tumour. Although in a recent report [17] some evidence has been presented that I G F II overexpression in Wilms tumour might be a tumour epiphenomenon, we argue that the rearrangement in the I G F II gene or in the vicinity of the gene might be responsible for elevated I G F II gene expression and consecutive tumour growth.…”
Section: Discussioncontrasting
confidence: 66%
“…In addition, they show a structural change of the I G F II gene in one Wilms tumour. Although in a recent report [17] some evidence has been presented that I G F II overexpression in Wilms tumour might be a tumour epiphenomenon, we argue that the rearrangement in the I G F II gene or in the vicinity of the gene might be responsible for elevated I G F II gene expression and consecutive tumour growth.…”
Section: Discussioncontrasting
confidence: 66%
“…Selection against such expression in a cell already transformed might be expected if IGF-II has the same suppressive effect on tumour formation in man as in an experimental situation. In support of this Little et al (1987) using xenografts of primary Wilms' tumours, were able to demonstrate that IGF-II expression was selected against during tumour passage, and they suggested that elevated IGF-II mRNA was not an essential component of tumour progression. Additionally, Maitland et al (1989) have reported the selective loss of chromosome 11 during maintenance of cell hybrids between normal human foetal kidney and HeLa cells as grafts in nude mice.…”
Section: Discussionmentioning
confidence: 90%
“….00 0. in WT progression (31), the levels of IGF-IR mRNA appear to correlate with the degree of differentiation of the tumor: tumors with heterologous elements and prominent stromal components are generally associated with higher levels of IGF-IR mRNA. This subset of tumors is mostly seen in the WAGR syndrome (1), a condition in which WT is associated with aniridia, genitourinary abnormalities, and mental retardation.…”
Section: Discussionmentioning
confidence: 99%